2013
DOI: 10.1097/pas.0b013e318299f2ab
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Myometrial Invasion as a Predictor of Lymph Node Metastasis or Extrauterine Disease in Low-grade Endometrial Carcinoma

Abstract: The purpose of this study was to examine predictors of lymph node metastases (LN+) or extrauterine disease (ED) in low grade (FIGO grades 1 or 2) endometrioid carcinoma (LGEC) in a multi institutional setting. For LGEC with and without LNM or ED, each of the 9 participating institutions evaluated patients age, tumor size, myometrial invasion (MI), FIGO grade, % solid component, the presence or absence of papillary architecture, microcystic elongated and fragmented glands (MELF) and single cell/cell cluster inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 35 publications
(79 reference statements)
8
77
0
2
Order By: Relevance
“…Similar results regarding tumor size and tumor stage were shown by others. 13,27 Furthermore, we could show a significant association between histology and lymph node involvement, with higher rates of lymph node metastasis in patients with nonendometrioid tumors. This pattern is well-known and has already been shown in several studies.…”
Section: Discussionmentioning
confidence: 63%
“…Similar results regarding tumor size and tumor stage were shown by others. 13,27 Furthermore, we could show a significant association between histology and lymph node involvement, with higher rates of lymph node metastasis in patients with nonendometrioid tumors. This pattern is well-known and has already been shown in several studies.…”
Section: Discussionmentioning
confidence: 63%
“…9 Another study confirmed that the MELF pattern of invasion was not an independent predictor of lymph node metastases. 10 However, other investigators have found an association between this pattern, lymphovascular invasion, as well as lymph node metastases. [11][12][13][14] In our experience, papillary ECa of intermediate grade, with or without MELF pattern, tends to be associated with vascular/lymphatic invasion and lymph node metastasis.…”
Section: Papillary Tumorsmentioning
confidence: 90%
“…Euscher and colleagues identified MELF in 70% of Grades 1 and 2 endometrioid adenocarcinomas with extrauterine spread or lymph node metastasis, in contrast to only 38% of tumors confined to the uterus (Po0.0001). However, the statistical significance was lost in a multivariate analysis of predictors of advanced stage disease(45). So we are left with intriguing but inconclusive results with respect to the biologic significance MELF or the fibromyxoid response.…”
mentioning
confidence: 96%